Pendidikan Spiritual : Menggetarkan Kalbu Dan Bermanfaat Bagi Sesama - Rohmat Rohmat (Millah: Journal of Religious Studies, 2015)
How religion in society has been an error in understanding religious symbols. Religion is understood as rescue individuals and not as a social blessing together, as if God is not present in social problems despite his name was mentioned everywhere, religion has become a stagnant spiritual message, symbolic expression without meaning. Researchers and social commentator gives his analysis that this phenomenon as the impact of modernity that led to the crisis of modern man’s spiritual so that they no longer know who he is, and the meaning of life. It can be said that all the missions of the core teachings of Islam on the doctrine of monotheism, morality and the law would basically lead to the moral education. That is why so it is said to have a close relationship and a depth between Islam and science of the soul, when we examine carefully that Sufism is part of moral education, in the process sufism are doing things that are related to moral education leads to character desired by al-Qur`an to get to be perfect man as the caliph as well as Abdullah.